2010
DOI: 10.1186/1476-9255-7-21
|View full text |Cite
|
Sign up to set email alerts
|

Captopril reduces cardiac inflammatory markers in spontaneously hypertensive rats by inactivation of NF-kB

Abstract: BackgroundCaptopril is an angiotensin-converting enzyme (ACE) inhibitor widely used in the treatment of arterial hypertension and cardiovascular diseases. Our objective was to study whether captopril is able to attenuate the cardiac inflammatory process associated with arterial hypertension.MethodsLeft ventricle mRNA expression and plasma levels of pro-inflammatory (interleukin-1β (IL-1β) and IL-6) and anti-inflammatory (IL-10) cytokines, were measured in spontaneously hypertensive rats (SHR) and their control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 60 publications
3
69
0
5
Order By: Relevance
“…Similar data were reported in the brain of normotensive rats (35,36). In addition, cardiac IL-1β and IL-6 mRNA levels were shown to increase in SHR (18), which was confirmed in this study. Val has been reported to decrease renal IL-1β mRNA expression in SHRSP (37) and vascular IL-1β and IL-6 mRNA expression in mice with vascular injury (38).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar data were reported in the brain of normotensive rats (35,36). In addition, cardiac IL-1β and IL-6 mRNA levels were shown to increase in SHR (18), which was confirmed in this study. Val has been reported to decrease renal IL-1β mRNA expression in SHRSP (37) and vascular IL-1β and IL-6 mRNA expression in mice with vascular injury (38).…”
Section: Discussionsupporting
confidence: 79%
“…It was reported that cardiac IL-1β and IL-6 mRNA levels are elevated in SHR rats compared to those in WKY rats (18). To evaluate the anti-inflammatory effects of Val and OM in SHRSP, we measured cardiac mRNA expression levels of IL-1β and IL-6 not only in SHRSP, but in normotensive WKY controls.…”
Section: Experiments 3 Effects Of Val and Om On Cardiac Il-1β And Il-mentioning
confidence: 99%
“…Indeed, clinical drugs inhibiting the Nox4/ROS-NF-κB pathway can be used in the treatment and/or prevention of atherosclerosis. For example, angiotensin-converting enzyme inhibitors, such as temocaprilat, or angiotensin Ⅱ receptor antagonists, such as olmesartan, not only inhibit the NADPH oxidase activity, including the p22phox expression, but also NF-κB activation, which induces the generation of ROS 41,42) . Statins also inhibit the NAPDH oxidase activity 43,44) and the activation of various related downstream signaling pathways, including that of p38 and ERK1/2, in order to produce anti-atherosclerotic effects 14,45) .…”
Section: Discussionmentioning
confidence: 99%
“…Additional smaller studies were considered in the absence of data from large-scale clinical trials. * E-COST Study achieved end-point prevention of stroke only in secondary prevention, not in primary Very recently, further data about the effects of captopril administration on rat, linked the anti-inflammatory effects of the ACEi with NF-B inactivation [217]. Left ventricle mRNA expression and plasma levels of pro-inflammatory (interleukin-1beta (IL1beta) and IL-6) and anti-inflammatory (IL-10) cytokines, were measured in spontaneously hypertensive rats (SHR) and their control normotensive, Wistar-Kyoto (WKY) rats, with or without a 12-week treatment with captopril (80 mg/Kg/day; n = six animals per group) In SHR, the observed increases in blood pressures, heart rate, left ventricle relative weight, plasma levels and cardiac mRNA expression of IL-1beta and IL-6, as well as the reductions in the plasma levels and in the cardiac mRNA expression of IL-10, were reversed after the treatment with captopril.…”
Section: Part IV -Anti-inflammatory Effects Of Ace-imentioning
confidence: 99%